(3TQM GdUajMIs - (3GdHZOGOj, GdcGXej, GdLhGO GdHZOGOj, LhGO Hf SYO Hf LhGO, J (B1065(3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3hcGfJ GdQSGdI GdeSeGI HGdUajMI HGdUajMI d (B... (3HgGA GdOjf eMeO GdYGedj (B...(3TQMJgG TQMG jPdd UYGHgG hjQaY GdMLGH Yf fbGHgG eSJeOG ef Gddg GdJhajb Efg GdgGOj Ydi ShGA GdWQjb , bGd GdeUfa QMeg Gddg (B...s
(3BNQgG (B:s
... (3hHYOeG YQaJ Cf GdhLg GdePchQ LGR eY GdGNJdGaj aj GdWhd ShGA GJabG aj GdYQV Ch dG jXgQ dc LQjGf GdMce aj LejY GdCbSGe GdSJI hMjK GfJgi cdGe GdeUfa (B.s
(3JHUQI GdYfhGf (B:s
(3GdUajMI dHgGA GdOjf eMeO GdYGedj (B((3aj GdGSWQdGH(B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\142s
(3GdPQjYI (B13\1338s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs